The Establishment Students’ Religious Character Through the Distinctive of Madrasah Activities - Ahmad Jamin; Zaini Zaini; Suriyadi Suriyadi; Musdizal Musdizal; Wisnarni Wisnarni (Tarbawi : Jurnal Ilmu Pendidikan, 2021)
The Distinctive of Madrasah is an extra-curricular activity with Islamic distinctive and character. This distinctive is designed to form the noble character of students based on Islamic values ​​in Madrasah. In the long term, the Distinctive of Madrasah is expected to contribute to preparing fully human resources as pillars in nation character building. This study aimed to describe the phenomena and experiences of managing the Distinctive of Madrasah activities at MAN I Sungai Penuh as a forum for establishment students' religious character. In this case, the researcher has used a qualitative research design with a phenomenological approach, trying to understand and describe the same experience about the management of the Distinctive of Madrasah activities as a means of establishing students' religious character. The data were collected by observation, interview, and documentation. Then, the informants of this study were the teachers and students at Madrasah Aliyah Negeri 1 Sungai Penuh, which consisted of 11 people. The data were analyzed by reducing, verifying, displaying, and drawing conclusions. The result of this study was the implementation of the Distinctive of Madrasah activities at MAN I Sungai Penuh, which consists of programmed activities, which are scheduled activities, measurable routines, and non-programmed activities in the form of daily routine activities, spontaneous and exemplary. Both activities are carried out in an integrated and synergized manner to strengthen the religious character of students. The continuous and continuous implementation of the Distinctive of Madrasah at MAN I Sungai Penuh has brought positive results with the establishment of students' religious character, which is marked by the increased understanding and charity of students' worship and an increased sense of togetherness, brotherhood, and caring among others both in daily life at Madrasah and home.